2020
DOI: 10.21203/rs.3.rs-80869/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crystal-Structures-Guided Design of Fragment-Based Drugs for Inhibiting the Main Protease of SARS-CoV-2

Abstract: Since the beginning of the COVID-19 pandemic, researchers and scientists across the globe are racing to find a cure for the highly contagious infectious disease caused by the SARS-CoV-2 virus. Despite many promising ongoing progress, there are currently no FDA approved drugs to treat infected patients. Among the various protein targets of SARS-CoV-2 virus, the main protease (Mpro) has attracted most interests. Recently, the crowdsourcing of drug discovery for inhibiting Mpro have yielded a plenty of drug frag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Finally, 17 molecules with binding abilities were found from which 15 molecules form a stable binding. Luan and Huynh, (2020) merged three-drug fragments (JFM, U0P, and HWH) into B19 which showed a slightly better free binding energy than the native peptide cleaved by the M pro .…”
Section: Potential Inhibitors Of Sars-cov-2 M Promentioning
confidence: 99%
“…Finally, 17 molecules with binding abilities were found from which 15 molecules form a stable binding. Luan and Huynh, (2020) merged three-drug fragments (JFM, U0P, and HWH) into B19 which showed a slightly better free binding energy than the native peptide cleaved by the M pro .…”
Section: Potential Inhibitors Of Sars-cov-2 M Promentioning
confidence: 99%
“…It was hypothesized that using appropriate linkers to join the fragment poses could provide a larger molecule whose divalent binding would encompass the interactions formed by its component domains. This approach has been used before for this protein, but only on a far more limited scale where three co-crystallized fragments were used to design 19 ligands (Luan & Huynh, 2020).…”
Section: Fragment Coupling and Linker Selectionmentioning
confidence: 99%
“…It was hypothesized that using appropriate linkers to join the fragment poses could provide relatively similar poses as constituting fragments. A previous relatively similar but limited study has reported using only three cocrystallized fragments to design 19 ligands [29].…”
Section: Fragment Coupling and Linker Selectionmentioning
confidence: 99%